The Tsunami - affected Burgher women of Dutch Bar, Batticaloa, Sri Lanka - Crusz, Robert (Colombo : Social Scientists' Association, 2009)
Study on Burgher women victims of Tsunami in Dutch Bar, Batticaloa, Sri Lanka.
Keywords: Women disaster victims -- Sri Lanka -- Dutch Bar (Batticaloa, Sri Lanka); Burghers (Sri Lankan people); Tsunami damage -- Sri Lanka -- Dutch Bar (Batticaloa); Indian Ocean Tsunami; Tsunami relief -- Sri Lanka -- Dutch Bar (Batticaloa)